Aplikasi Penerjemah Tablatur Gitar Menggunakan Teknologi Augmented Reality Pada Platform Android - Bagus Setiadi; Eko Budi Setiawan (ULTIMA InfoSys, 2016)
The guitar tablature is a guitar melody guitar used by professional guitarists when performing. Guitar tablature translator application is one of the media to help users especially novice guitarist to translate the guitar tablature. This application is built on android platform using Augmented Reality technology with Markerless Augmented Realty method to combine virtual world objects into the real world. In this application there are several functions such as displaying finger position information, 2D objects and audio. Index Terms—Tablatur Gitar, Augmented Reality, Android.